Back Cover: Ann. Phys. 1‐2'2013. Issue 1 (8th February 2013) - Hommelhoff, Peter; Kling, Matthias; Stockman, Mark
<x xml:space="preserve">Abstract</x> In short‐pulse laser ablation, by virtue of the ultrafast excitation of abundant free electrons, plasmonic effects may arise spontaneously and contribute greatly to the reducing of laser‐induced surface structures beyond the diffraction limit. In the figure, referring to the laser‐induced subwavelength grating that exhibits an evident grating‐splitting evolution, a physical picture for the grating‐splitting phenomenon is shown: on the metallic grating excited by ultrashort laser pulses, surface plasmon modes are able to evolve from the resonant to the nonresonant mode and further to the inphase or antiphase asymmetric mode. Picture: M. Huang et al., 10.1002/andp.201200136, p. 74, in this issue <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>